Biochanin a Enhances the Defense Against Salmonella enterica Infection Through AMPK/ULK1/mTOR-Mediated Autophagy and Extracellular Traps and Reversing SPI-1-Dependent Macrophage (MΦ) M2 Polarization - Zhao, Xingchen; Tang, Xudong; Guo, Na; An, Yanan; Chen, Xiangrong; Shi, Ce; Wang, Chao; Li, Yan; Li, Shulin; Xu, Hongyue; Liu, Mingyuan; Wang, Yang; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
A novel treatment regimen for bacterial infections is the pharmacological enhancement of the host’s immune defenses. We demonstrated that biochanin A (BCA), an isoflavone constituent in some plants, could enhance both intra- and extracellular bactericidal activity of host cells. First, BCA could induce a complete autophagic response in nonphagocytic cells (HeLa) or macrophages (MФs) via the AMPK/ULK1/mTOR pathway and Beclin-1-dependent manner, and BCA enhanced the killing of invading Salmonella by autophagy through reinforcing ubiquitinated adapter protein (LRSAM1, NDP52 and p62)-mediated recognition of intracellular bacteria and through the formation of autophagolysosomes. Second, we demonstrated that BCA could enhance the release of MФ extracellular traps (METs) to remove extracellular Salmonella also via the AMPK/ULK1/mTOR pathway, not through reactive oxygen species (ROS) pathway. Furtherly, in a Salmonella-infected mouse model, BCA treatment increased intra- and extracellular bactericidal activity through the strengthening autophagy and MET production, respectively, in peritoneal MФs, liver and spleen tissue. Additionally, our findings showed that BCA downregulated SPI-1 (Salmonella pathogenicity island 1) expression during Salmonella infection in vitro and in vivo to reverse the MФ M2 polarization, which was different from the MФ M1 phenotype caused by most of bacteria infection. Together, these findings suggest that BCA has an immunomodulatory effect on Salmonella-infected host cells and enhances their bactericidal activity in vitro and in vivo through autophagy, extracellular traps and regulation of MФ polarization.